Screening Penyakit Tidak Menular (PTM) Dan Konseling Kesehatan Pada Civitas Academica STIKes Widya Dharma Husada Tangerang - Pratiwi, Rita Dwi; Andriati, Riris; Indah, Fenita Purnama Sari; Aulia, Gina; Ismaya, Nurwulan Adi; Ayuningtyas, Gita; Romlah, Siti Novy; Handoyo, Lukman; Listiana, Ida; Fitriani, Dewi; Hasanah, Uswatun; Veri, Veri; Kuntoadi, Gama Bagus; Sucipto, Sucipto; Sheli, Sheli; Alita, Dini Arum; Lestari, Puji; Ramdan, Raka Fahri; Hidayat, Asep (Pelita Masyarakat, 2024)
This community service activity is conducted regularly every semester by lecturers involving 450 students from various study programs, collaborating with local health centers (Puskesmas) in South Tangerang. The purpose of the activity is to conduct health screenings to prevent and control Non-Communicable Diseases (NCDs) such as anemia, hypertension, diabetes mellitus, and obesity. The methods used include health education for students on NCD prevention and control, measurements of height, weight, upper arm circumference, blood pressure checks, random blood glucose tests, and a questionnaire on smoking habits. The results showed that 3 participants had a history of hypertension and 1 had diabetes mellitus. Additionally, 23 participants were identified as being at risk of chronic diseases. Follow-up actions included in-depth counseling and referral to the nearest Puskesmas. All participants were also found to be non-smokers. This activity aims to raise awareness about NCD prevention, followed by further health checks and sponsorship support in the future.